Diffusion-assisted growth of periodic patterns on metal surfaces. (15th April 2023) - Qian, Wei; Zheng, Pengfei; Gao, Ning; Setyawan, Wahyu; Chen, Peng; Liu, Xing; Liu, Yong; Sun, Liangting; Liu, Ming; Che, Tong; Wei, Ran; Chen, Jiming
Abstract: Periodic patterns formed on various solid surfaces could seriously affect the properties of materials. Understanding the underlying mechanism is a key step to apply and control pattern formation in many fields. In this work, periodic patterns induced by low-energy plasma exposures on tungsten surfaces are observed and related new formation mechanisms are developed. Results from experiments and computer simulations demonstrate that atom diffusion accelerated by low energy and high flux exposures is the dominant mechanism for pattern formation. Furthermore, a similar pattern formation has been confirmed by plasma exposure experiments on molybdenum. Based on this mechanism, patterns with controllable shape have been successfully prepared on tungsten surface by adjusting plasma exposure parameters, which may provide a new understanding of pattern formation and related surface damage in tungsten induced by plasma exposures. Graphical abstract: Image, graphical abstract